A New Dimeric Secoiridoid Glycoside from the Leaves of Olea ferrugineaRoyle. Issue 5 (May 2015) - Hashmi, Muhammad A.; Hameed, Rabia; Khan, Afsar; Farooq, Umar; Ahmad, Viqar U.; Perveen, Shagufta
Abstract A new dimeric secoiridoid glycoside, trivially named oleferrugine B (1), has been isolated from the AcOEt‐soluble part of the MeOH extract of leaves of Olea ferrugineaRoyle. The structure of the isolated compound was established on the basis of ESI‐MS fragmentation patterns, and 1D‐ and 2D‐NMR techniques, including 1H‐ and 13C‐NMR, HSQC, 1H, 1H‐COSY, HMBC, and NOESY experiments, and by comparison with literature data.